A morphometric analysis of Hylarana signata group (previously known as Rana signata and Rana picturata) of Malaysia - Ramlah, Zainudin; Siti Nurlydia, Sazali (World Scientific Publishing Company, 2012)
A study on morphometrical variations of Malaysian Hylarana signata group was conducted to reveal the morphological relationships within the species group. Twenty-seven morphological characters from 18 individuals of H. signata and H. picturata were measured and recorded. The numerical data were analysed using Discriminant Function Analysis in SPSS program version 16.0 and UPGMA Cluster Analysis in Minitab program version 14.0. The results show the complexity clustering between the examined species that might be due to ancient polymorphism of the lineages or cryptic species within the group. Hence, further study should include more representatives in order to fully elucidate the morphological relationships of H. signata group.